Peran Pekerja Sosial dalam Penanganan Lansia Komorbid Covid-19 melalui Program Jiwong Jiga di Purwokerto Wetan: The Role of Social Workers in Handling the Comorbid Elderly with Covid-19 through the Jiwong Jiga Program in Purwokerto Wetan - Siti Aisyah Rizkotul Amalia (CV Omah Kreaor, 2025)
This study aims to analyze the role of social workers in assisting elderly individuals with comorbidities through the Jiwong Jiga application in Purwokerto Wetan, as an effort to reduce the spread of Covid-19. Elderly people with comorbid conditions are highly vulnerable to Covid-19 infection, thus requiring community-based approaches for their care and protection. The Jiwong Jiga application, meaning